Age Recognition in Adults with Intellectual Disabilities: A Literature Review and an Exploratory Study - Bell, D; Espie, C (2000)
The ability of children to classify accurately their own ages and the ages of others has been the subject of very limited research. However, the literature is largely in agreement on there being progressive increases in skill with chronological age, although there is disagreement on the age at which this ability becomes well developed. The processes look similar in the field of intellectual disabilities, although this area is extremely under-researched. Key factors may include age, the amount of time spent in institutions (e.g. long-term hospitals for people with intellectual disabilities), developmental level and IQ. The present paper provides a review of the relevant literature and an exploratory study investigating the age recognition of self and colleagues in a group of 20 adults with intellectual disability, some from within what has been a major hospital for people with intellectual disabilities and some from the wider community. Measures of age recognition using photographs, as well as standardized measures of intellectual ability and social adaptive behaviour, were administered, and correlations were found between the ability to recognize age in others and developmental age, and also IQ. Success on the task of age discrimination appears to be more likely if the IQ of the individual is around 60-65 or above, and if the person shows social adaptive behaviour equivalent to 8 or 9 years of age and over. Also included in the study was a task in which only the discrimination of whether the photographs were of adults or children was required, and this proved to be a simpler process for the participants. The present study also demonstrates some of the discriminative stimuli used by adults with intellectual disabilities to ascertain the approximate age of a person.